TECHNIQUES AND METHODS OF INCREASING MOTIVATION AMONG FOREIGN-SPEAKING SCHOOLCHILDREN IN THE STUDY OF THE VOCABULARY OF THE MODERN RUSSIAN LANGUAGE (Innovative Technologica: Methodical Research Journal, 2023)
Russian Russian the article discusses techniques and methods of increasing motivation among foreign-speaking schoolchildren when studying the vocabulary of the modern Russian language, and also provides lexical tasks that help the teacher to increase motivation to learn Russian in a foreign-speaking audience.